Baicalein protects renal tubular epithelial cells againsthypoxia-reoxygenation injury. (15th October 2018) - Chen, Chun; Cai, Chudan; Lin, Hanfei; Zhang, Weidai; Peng, Yanqiang; Wu, Kefei
Abstract: Background: To investigate the protective effects and mechanism of baicalein (BAI), a naturally occurring flavonoid, against hypoxia-reoxygenation (HR) injury in renal tubular epithelial cells (HK-2). Methods: Cultured human renal proximal tubular cell line HK-2 was exposed to 24 h of hypoxia (5% CO2, 1% O2, and 94% N2 ), followed by 12 h of reoxygenation (5% CO2, 21% O2, and 74% N2 ). HK-2 cells were divided into three groups: control, HR, and HR-BAI (0.3 µg/ml). Reactive oxygen species (ROS) were measured and cell apoptosis was analyzed by flow cytometry and morphology. ELISAs were performed to determine the levels of IL-1, intercellular adhesion molecule-1 (ICAM-1), and monocyte chemotactic protein-1 (MCP-1). IL-1β, ICAM-1, and MCP-1 mRNA levels were determined by real-time quantitative PCR. Results: HK-2 cells that underwent HR exhibited increases in IL-1β expression by 0.94%, ROS by 0.59%, ICAM-1 expression by 0.8%, and MCP-1 expression by 1.2%. Moreover, HK-2 cell apoptosis was increased after HR ( p  < .05). Compared with the HR group, BAI treatment reduced the elevation of oxidative stress (ROS) by 0.76%, as well as HR-mediated induction of IL-1β and apoptosis of HK2 cells. Protein and mRNA levels of ICAM-1 and MCP-1 were also reduced. Conclusions: BAI protects renal tubular epithelial cells from HR injury by reducing inflammatory cytokine expression and oxidative stress.